Media Psychological Expertise Audio-Visual Products - Chaplinska, Iuliia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article raises the current problem for Ukrainian society as the mechanisms of media regulators, which cover sensitive topics that may adversely affect the psychological and moral development of children. The author reviews scientific research related to the negative impact of television programs on child development and justifies the need for media psychological expertise to protect children in the information space and the ability to defend this right in court.The main purpose of the article is to substantiate the scientific construct of media psychological expertise. In connection with this purpose the author presents its methodological principles: typology of leading types of visual, audiovisual mass media and algorithms of visual media texts research, classification of information destructive influences of media (Cherepovska), five planes of film analysis (Chaplinskaya), different types of analysis of media texts (Fedorov) and detailed typology of audiovisual media perception (Hilko), age periodization of media risks and criteria for harming the psychological well-being of children with media products (Naidenova), as well as methods of psychological research in cases of moral suffering to the person (Savkina et al.).The author defines the scientific construct of media psychological examination, describes its object, subject, list of main tasks, methods, process and substantiates the requirements for the competence of the expert.Prospects for research on this topic were outlined in the form of supplementing the procedure of media psychological examination, formation of a psychodiagnostic minimum for the examination of minors, development of curricula for experts, and perhaps the formation of a separate discipline for higher education.
Keywords: media psychology; media risks; children; security; audiovisual products; psychological harm; psychological well-being; media psychological expertise